The order Carnivora (Mammalia) in Peru: State of Knowledge and research priorities for its conservation - Cossíos, E. Daniel (2012)
The high diversity of Peruvian carnivore species may pose problems when deciding to which taxa and topics new research efforts should be directed. In this publication, we evaluated the research effort made on each taxa -by assessing the number of publications per species-, point out the knowledge gaps that are important to the conservation of each species and present the first evaluation of research priorities for this group of animals to the country. We registered 145 publications about Peruvian carnivores made since 1943. The number of publications is significantly different between taxa, between subjects and between ecoregions where the research was conducted. According to the proposed priority scale, the species to be studied with greater priority is Nasua olivacea and the lowest priority is for Leopardus pardalis. The results of our study highlight the urgent need to conduct research on certain species of carnivores about which there are few published data, locally and globally, and which occupy a low number of ecoregions in the country. Both the scale of research priorities and the list of knowledge gaps presented here will be useful to guide logistical and financial efforts, for individual researchers as well as for private or governmental institutions.